Avaliação do perfil de linfócitos T e células NK na anemia falciforme - Percout, Priscila Oliveira (2017)
Introduction: Sickle cell anemia (SCA) is one of the most common genetic disorders in the world. However, until recently, only the direct consequences of the deoxyHbS polymerization was used to explain the pathophysiology of the disease. Currently, it is known that the clinical repercussions of FA involve complex interactions between the erythrocyte, endothelium and leukocytes: cytokines secreted by inflammatory cells are involved in SCA crisis and in the maintenance of a systemic inflammatory status, suggesting that T cells (Helpers and Cytotoxics) and NK have a fundalmental role in the clinical phenomena of SCA. This study aims to evaluate the profile of T and NK lymphocytes in patients with AF and compare them with the profile of individuals with sickle cell trait and individuals without hemoglobinopathies. Materials and methods: Peripheral blood was collected from 13 individuals; 7 with SS hemoglobinopathy (SS group), 5 with sickle cell trait (AS group) and 5 normal (AA group). The lymphocytes isolation for analysis was performed using Ficoll-Hypaque solution. Immunophenotyping for the determination of lymphocyte subtypes was performed by flow cytometry, using eight-color cytometer and eight BD Biosciences antibodies. Data were analyzed using Flowjo software and tabulated in SPSS IBM 22.0. The results referring to the numerical variables were expressed through measures of central tendency. Results: A lower frequency of T lymphocytes and a greater frequency of NK cells were observed in sickle cell patients.The variation of TCD4 + found between the SCA and the AA group was significant (p = 0.04). Lower frequency tendency in patients of the SS group remained for B lymphocytes. A higher frequency of NK cells was observed in patients with sickle cell anemia (mean: group AA = 15.63%, group AS = 14.82% and group SS = 23.34%) with statistically significant variation. Conclusion: SCA patients present a lower frequency of CD4 + CD8 + T cells and TNK cells when compared with HbAS individuals and individuals without hemoglobinopathies. An increasing and progressive frequency of NK cells is observed between groups AA, AS and SS. We believe that further studies are needed to understand the role of these cells in the genesis of systemic inflammation of SCA. This understanding may contribute to the development of new therapeutic strategies.